Article comprising a substrate and a member formed on the substrate

The article with a glass matrix and oriented inorganic filler achieves both insulation and heat dissipation in thin components, addressing the challenge of miniaturization in electronic components.

JP7600022B2Active Publication Date: 2024-12-16NORITAKE MACHINE TECHNO CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
JP2021061907
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2021-03-31
Publication Date
2024-12-16
Estimated Expiration
2041-03-31

AI Technical Summary

Technical Problem

There is a demand for thinner electronic components with excellent insulation and heat dissipation properties, which existing technologies struggle to achieve simultaneously.

Method used

An article comprising a base material with a plate-shaped member containing a glass matrix and inorganic filler, where the inorganic filler has an average aspect ratio of 0.005 to 0.5 and is oriented within 10° to the cross-section, ensuring efficient heat conduction and insulation.

Benefits of technology

The solution provides both excellent insulation and heat dissipation properties, even in thin layers, with improved bondability to the base material.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007600022000004
    Figure 0007600022000004
  • Figure 0007600022000005
    Figure 0007600022000005
  • Figure 0007600022000006
    Figure 0007600022000006
Patent Text Reader

Abstract

To provide an article having a member which can suitably achieve both of an insulating property and a heat dissipating property even in the form of e.g. a thinned layer.SOLUTION: An article 1 disclosed herein comprises: a base material 12; and a plate-like member 10 formed on the base material and containing a glass matrix and inorganic filler. The inorganic filler has an average aspect ratio (the ratio of Short diameter / Long diameter) of 0.005-0.5. About 90% or more of the inorganic filler in number, observed in a SEM image of a cross section taken along a thickness direction of the member, an acute angle θ formed by a long diameter of the inorganic filler and one of the thickness direction and a direction orthogonal to the cross section is within 10°.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to an article including a substrate and a member formed on the substrate. [Background technology]

[0002] For example, when mounting a circuit board, a planar heater, or the like on an electronic component, it is necessary to ensure insulation from the surrounding components as appropriate. One example of a method for ensuring insulation is a method of mounting via an insulating component. One such component is, for example, a glass ceramic substrate provided with a fired material containing alumina particles and a glass component (see Patent Document 1 below). [Prior art documents] [Patent documents]

[0003] [Patent Document 1] JP 2020-019688 A Summary of the Invention [Problem to be solved by the invention]

[0004] In recent years, there has been a demand for further miniaturization of electronic components. Accordingly, there is a demand for thinner layers of members of electronic components (for example, a thickness of 200 μm or less, preferably about 100 μm or less). That is, even in such a thin-layered form, the members have excellent insulation properties and excellent heat dissipation properties (i.e., thermal conductivity).

[0005] The present invention has been made in consideration of the above circumstances, and its main object is to provide an article having a member that can preferably achieve both insulating properties and heat dissipation properties, even in a thin-layered form, for example. [Means for solving the problem]

[0006] In order to achieve this object, the present invention provides an article comprising a substrate and a plate-like member formed on the substrate, the plate-like member containing a glass matrix and an inorganic filler, wherein the inorganic filler has an average aspect ratio (minor axis / major axis ratio) of 0.005 to 0.5, and 90% or more of the inorganic fillers observed in an SEM image of a cross section in the thickness direction of the member have an acute angle θ of 10° or less between the major axis of the inorganic filler and either the thickness direction or the direction perpendicular to the cross section (hereinafter, also simply referred to as "having orientation").

[0007] The present inventors have found that a member containing an inorganic filler having an appropriately adjusted average aspect ratio and the above-mentioned orientation can provide both insulating properties and heat dissipation properties, and have completed the present invention. Although it is not intended to be particularly limited, it is believed that the inorganic filler having such orientation allows the generated heat to be efficiently conducted along the direction in which the inorganic filler is oriented. This is believed to result in excellent heat dissipation properties.

[0008] In a preferred embodiment of the article disclosed herein, the inorganic filler has an average minor axis of 0.01 μm or more and an average major axis of 20 μm or less. In another preferred embodiment, the average major axis is in the range of 1 μm to 20 μm. An article having a member containing an inorganic filler of this configuration is preferred because it more suitably achieves both insulation and heat dissipation.

[0009] In a preferred embodiment of the article disclosed herein, when the ratio of the area occupied by the inorganic filler in an SEM image of the cross section of the member in a direction perpendicular to the cross section in the thickness direction is calculated based on the following formula: area occupation ratio = (total area of ​​inorganic filler / total area of ​​observation field) x 100 (%), the area occupation ratio is within a range of 15 to 70%. A member having such a configuration is preferable because it has excellent bonding with the substrate in addition to achieving both insulation and heat dissipation properties.

[0010] In a preferred embodiment of the article disclosed herein, the glass powder constituting the glass matrix contains a B2O3-SiO2-based glass. A member containing a glass matrix made of such glass powder is preferred because it has excellent bonding properties with a substrate made of a metal material, for example.

[0011] In a preferred embodiment of the article disclosed herein, the thermal expansion coefficient of the glass powder constituting the glass matrix from 30° C. to 500° C. is 0.3×10 ―5 K ―1 ~2.0×10 ―5 K ―1 A member containing a glass matrix made of glass powder having a thermal expansion coefficient within the above range is preferable because it has excellent bonding properties with a base material made of a metal material, for example.

[0012] In a preferred embodiment of the article disclosed herein, the substrate is made of a metal material (including a single metal material or an alloy material such as a steel material containing two or more elements). An article having such a substrate is preferred because it can be used for various purposes.

[0013] In a preferred embodiment of the article disclosed herein, the average thickness of the member is 100 μm or less. An article including a member having such an average thickness is suitable as a target to which the technology disclosed herein is applied. [Brief description of the drawings]

[0014] [Figure 1] FIG. 1 is a cross-sectional view illustrating an article according to an embodiment. [Figure 2A] FIG. 2 is a schematic diagram showing an inorganic filler oriented in a direction perpendicular to a cross section in the thickness direction of a member. [Figure 2B] FIG. 2 is a schematic diagram showing an inorganic filler oriented in the thickness direction of a member. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0015] Hereinafter, preferred embodiments of the present invention will be described. Matters other than those specifically mentioned in this specification and that are necessary for the implementation of the present invention can be understood as design matters of those skilled in the art based on the prior art in the relevant field. The present invention can be implemented based on the content disclosed in this specification and the common general knowledge in the relevant field. Note that the following embodiments are not intended to limit the technology disclosed herein to such embodiments. Also, in the drawings shown in this specification, members and parts having the same function are denoted by the same reference numerals for explanation. And the dimensional relationships (length, width, thickness, etc.) in each figure do not reflect the actual dimensional relationships. In this specification and the claims, when a predetermined numerical range is denoted as A~B (A and B are arbitrary numerical values), it means A or more and B or less. Therefore, it includes cases where it exceeds A and is less than B.

[0016] <Article 1> FIG. 1 is a cross-sectional view schematically showing Article 1 according to one embodiment. As shown in the figure, Article 1 according to this embodiment generally includes a base material 12 and a member 10 formed on the base material and containing a glass matrix and an inorganic filler. Hereinafter, each component will be described in detail.

[0017] (Member 10) The member 10 according to this embodiment is a plate-shaped member including a glass matrix (not shown) and an inorganic filler 20 contained in the glass matrix. Here, "plate-shaped" in this specification and the claims can refer to a mode having two wide surfaces and having a thickness between the wide surfaces. Such wide surfaces can have various shapes such as rectangular, circular, and elliptical. Also, although not particularly limited, when the major axis of the wide surface is s, the minor axis is t, and the thickness is u, generally u < t < s can be satisfied. Also, such u can be u ≤ (1 / 2)t, u ≤ (1 / 3)t, u ≤ (1 / 5)t, etc.

[0018] The glass powder constituting the glass matrix is ​​not particularly limited as long as the effects of the technology disclosed herein are exhibited, but a suitable example is B2O3-SiO2-based glass containing boron (B2O3) and silicon (SiO2) as main components. The member 10 containing such B2O3-SiO2-based glass is preferred because it has excellent adhesion to the surface of the substrate 12.

[0019] More specifically, the boron component (B2O3) contributes to increasing the fluidity during firing, and therefore can improve the fixation of the member 10 to the surface of the substrate 12. The proportion of B2O3 in the B2O3-SiO2-based glass is preferably 1 mol% or more, more preferably 5 mol% or more, and particularly preferably 10 mol% or more, in terms of the molar ratio of oxide. This can more suitably improve the fixation of the member 10 after firing. On the other hand, if the content of B2O3 is excessive, it may become difficult to maintain the shape of the member 10 during firing. For this reason, the upper limit of the proportion of B2O3 in the B2O3-SiO2-based glass is preferably 25 mol% or less, more preferably 20 mol% or less, and particularly preferably 15 mol% or less.

[0020] Next, the silicon component (SiO2) is a component that constitutes the skeleton of the glass layer after firing. SiO2 also has a function of improving the fixation to the surface of the substrate. The ratio of SiO2 in the B2O3-SiO2-based glass is preferably 10 mol% or more, more preferably 20 mol% or more, in terms of the molar ratio of oxide. This can further improve the fixation to the surface of the substrate 12. The upper limit of the ratio of SiO2 is preferably 80 mol% or less, more preferably 70 mol% or less, and particularly preferably 60 mol% or less. The B2O3-SiO2-based glass may also contain components other than B2O3 and SiO2. Examples of such other components include oxides of group 2 elements (RO:R is Mg, Ca, Sr, Ba, Ra, etc.), aluminum components (Al2O3), yttrium components (Y2O3), zinc components (ZnO), etc. By adjusting the content of these other components, the heat resistance and chemical durability of the member 10 after firing can be improved.

[0021] The glass powder is not limited to the above-mentioned B2O3-SiO2-based glass, and conventionally known glass powders can be used without any particular limitation. For example, the glass powder may be a crystallized glass containing crystals in addition to a general amorphous glass. The components of the glass powder are also not particularly limited. Other examples of the glass powder include SiO2-RO-based glass, SiO2-RO-Al2O3-based glass, SiO2-RO-Y2O3-based glass, SiO2-RO-B2O3-based glass, SiO2-RO-Al2O3-B2O3-based glass, SiO2-Al2O3-based glass, SiO2-ZnO-based glass, and SiO2-ZrO2-based glass. The average particle size of the glass powder is not particularly limited as long as the effect of the technology disclosed herein is exhibited, but can be about 0.1 to 10 μm (for example, about 0.5 to 5.0 μm). In this specification, the term "average particle size" refers to the particle size D50 value (also referred to as the median size) corresponding to the cumulative 50% from the fine particle side with a small particle size in the volume-based particle size distribution measured based on a laser diffraction / light scattering method.

[0022] The inorganic filler 20 is not particularly limited as long as the effect of the technology disclosed herein is exhibited, and examples thereof include alumina, silica, titanium oxide, yttrium oxide, zirconia, zirconia stabilized by yttrium or other rare earth elements, magnesia, barium sulfate, aluminum hydroxide, and the like. Among them, alumina and zirconia, which are highly versatile, can be preferably used. These can be used alone or in combination of two or more. The content ratio of the zirconia stabilizer is not particularly limited, but is preferably about 5 to 10 mol % when the entire inorganic filler is taken as 100 mol %. In addition, the crystallinity of the inorganic filler 20 is not particularly limited as long as the effect of the technology disclosed herein is exhibited, and may be single crystal or polycrystal, but from the viewpoint of improving the mechanical strength of the member 10, a single crystal is preferably used.

[0023] The thermal expansion coefficient of the glass powder constituting the glass matrix is ​​not particularly limited as long as the effects of the technology disclosed herein are exhibited, but it is preferable that the thermal expansion coefficient is close to that of the substrate to be coated. The thermal expansion coefficient of the glass powder is, for example, 0.3×10 -5 K -1 ~2.0×10 -5 K -1 (For example, 0.5×10 -5 K -1 ~2.0×10 -5 K -1 etc. A member containing a glass matrix made of glass powder with a thermal expansion coefficient within the above range is preferable because it has excellent bonding properties with a substrate made of a metal material, for example. In this specification, the term "thermal expansion coefficient" refers to the average expansion coefficient (average linear expansion coefficient) measured using a thermomechanical analysis (TMA) in a temperature range from 30°C to 500°C, and refers to the value obtained by dividing the amount of change in the sample length relative to the initial length of the sample by the temperature difference. The thermal expansion coefficient can be measured, for example, in accordance with JIS R3102:1995, etc.

[0024] The inorganic filler 20 has an average minor axis / major axis ratio (i.e., average aspect ratio) of 0.005 to 0.5. Although not particularly limited, from the viewpoint of more suitably improving the mechanical strength of the member 10, the average aspect ratio is preferably 0.01 or more, for example 0.02 or more. From the viewpoint of improving heat dissipation, the average aspect ratio is preferably 0.4 or less, for example 0.2 or less, 0.1 or less, or 0.05 or less.

[0025] In the present specification and claims, the term "average aspect ratio" refers to the average value of the minor axis / major axis ratio of a plurality of particles. That is, the average aspect ratio is a value indicating the average particle shape of the particles. From the above average aspect ratio, the inorganic filler particles may have various shapes, such as flat, scaly, flake-like, rod-like, elliptical, fibrous, and needle-like shapes. Among them, from the viewpoint of easily providing orientation, flat, scaly, flake-like, and the like shapes are preferred.

[0026] The average aspect ratio can be determined, for example, by electron microscope observation. As a specific procedure, for example, a scanning electron microscope (SEM) is used to observe a predetermined number of particles (for example, 50 or more) contained in the inorganic filler to be measured, and a rectangle with the smallest circumscribing area is drawn for each particle image. Then, for the rectangle drawn for each particle image, the length of the short side (minor axis value) is divided by the length of the long side (major axis value) to calculate the minor axis / major axis ratio (aspect ratio) of each particle. Then, the average aspect ratio can be determined by arithmetically averaging the aspect ratios of the predetermined number of particles. The aspect ratio and average aspect ratio of each particle can be determined using general image analysis software. When the inorganic filler particles are, for example, flat, scaly, flake-like, rod-like, elliptical, etc., the minor axis and major axis of the broad surface are calculated.

[0027] The average value of the minor axis of the inorganic filler 20 (i.e., the average minor axis) is not particularly limited as long as the effects of the technology disclosed herein are exerted, but is generally 0.01 μm or more, for example, 0.04 μm or more (0.05 μm or more), and from the viewpoint of more suitably ensuring insulation, it can be preferably 0.1 μm or more, more preferably 0.2 μm or more. The upper limit of the average minor axis is not particularly limited as long as the effects of the technology disclosed herein are exerted, but can be generally 10 μm or less, for example, 5 μm or less, 4 μm or less.

[0028] In the present specification and claims, the term "average minor axis" refers to the average minor axis of a plurality of particles (e.g., 50 or more). The minor axis of each particle can be calculated as the arithmetic average of the lengths of the short sides of the rectangle that circumscribes each particle image obtained by SEM and has the smallest area, similar to the aspect ratio described above.

[0029] The average value of the major axis of the inorganic filler 20 (i.e., the average major axis) is not particularly limited as long as the effects of the technology disclosed herein are exhibited, but is generally 0.1 μm or more, for example 0.5 μm or more, and from the viewpoint of more favorably ensuring insulation and heat dissipation, it can be preferably 1 μm or more, more preferably 5 μm or more. The upper limit of the average major axis is not particularly limited as long as the effects of the technology disclosed herein are exhibited, but it can be generally 30 μm or less, preferably 20 μm or less, for example 10 μm or less. That is, the average value of the major axis can be preferably 1 μm to 20 μm.

[0030] In the present specification and claims, the term "average major axis" refers to the average value of the major axes of a plurality of particles (e.g., 50 or more). The major axis of each particle can be calculated as the arithmetic average value of the lengths of the long sides of the rectangles that circumscribe each particle image obtained by SEM and have the smallest area, similar to the aspect ratio described above.

[0031] The average thickness (i.e., average thickness) of the inorganic filler 20 is not particularly limited as long as the effects of the technology disclosed herein are exhibited, but can be about 0.01 μm or more, for example, 0.03 μm or more. The upper limit of the average thickness is not particularly limited as long as the effects of the technology disclosed herein are exhibited, but can be about 0.1 μm or less, for example, 0.05 μm or less.

[0032] In addition, the "average thickness" in this specification refers to the average value of the thicknesses of a plurality of (for example, 50 or more) particles. The average thickness of each particle can be determined by electron microscope (SEM) observation. As a specific procedure, for example, a sample in which the particles to be measured are solidified with resin is prepared, and the cross-section of the sample is observed with a scanning electron microscope. Then, the thickness (the length across the thickest part) of a predetermined number (for example, 50 or more) of particles contained in the cross-section is measured, and the average thickness can be obtained by arithmetically averaging the thicknesses of the predetermined number of particles. Regarding the thickness of the inorganic filler particles, for example, when the inorganic filler is in the shape of a flat plate, scale, flake, rod, ellipse, etc., it can be referred to as the length between the wide surfaces. Also, although not particularly limited, when the major axis of the inorganic filler is s, the minor axis is t, and the thickness is u, generally u < t < s can be obtained. And although not particularly limited, u ≤ 1 / 2t, u ≤ (1 / 3)t, u ≤ 1 / 5t, etc. can be set.

[0033] Also, for 90% or more of the inorganic fillers 20 observed in the SEM image of the cross-section (i.e., the XY plane) in the thickness direction (i.e., the Y direction) of the member 10, for 90% or more of the inorganic fillers, the acute angle θ formed by the major axis of the inorganic filler with respect to either one of the thickness direction or the direction orthogonal to the cross-section (the angle θ formed by the inorganic filler 20a in Fig. 2A a , the angle θ formed by the inorganic filler 20b in Fig. 2B b(see ) is within 10°. The SEM image is to be randomly acquired at least one. The magnification of the SEM image is not particularly limited, but may be, for example, about 1000 to 5000. According to an embodiment in which the value of θ is 10° or less, an article having a member that satisfies both insulation and heat dissipation can be obtained. The value of θ may be 10° or less, and from the viewpoint of more suitably realizing the heat dissipation of the article, it may be preferably 9° or less, more preferably 7° or less. The above description of "90% by number or more" may mean that, when the number of inorganic fillers confirmed in the SEM image is n, 0.9×n or more. For example, when n=20, the value of θ of 18 or more may be 10° or less. The value of n cannot be generally defined because it depends on the cross section to be measured, but from the viewpoint of improving measurement accuracy and reproducibility, it is preferably 20 or more, more preferably 30 or more, and even more preferably 50 or more (for example, 100 or more). Furthermore, for example, when two or more SEM images are obtained, the number of inorganic fillers observed in each image is counted, and the θ value of 90% or more of the total should be 10° or less.

[0034] In a preferred embodiment, when the ratio of the area occupied by the inorganic filler 50 in an SEM image of a cross section of the member 10 in a direction perpendicular to the cross section in the thickness direction (i.e., the XY cross section) is calculated based on the following formula: area occupation ratio=(total area of ​​inorganic filler / total area of ​​observation field)×100(%), the area occupation ratio is within a range of 15 to 70%. The member 10 having such a configuration is preferable because it has excellent bonding properties with the base material 12 in addition to achieving both insulation and heat dissipation properties. Moreover, from the viewpoint of improving such bonding properties, the area occupation ratio can more preferably be within a range of 15 to 50%. For details on the method of calculating such area occupation ratio, please refer to the examples described later.

[0035] In addition, the member 10 may contain other components as long as they do not significantly impair the effects of the technology disclosed herein. For example, when particulate components other than inorganic fillers are contained as such optional components, it is preferable that the particulate components also have an average aspect ratio similar to that of the inorganic filler. Note that the other components can be selected from conventionally known components that can be contained in this type of member without any particular restrictions, and detailed explanations are omitted since they do not limit the technology disclosed herein.

[0036] The average thickness of the member 10 (i.e., the length in the Y direction) is not particularly limited, but when used in, for example, miniaturized electronic components, it can be approximately 200 μm or less, preferably 150 μm or less, more preferably 100 μm or less, 80 μm or less, 70 μm or less, 60 μm or less, and particularly preferably 50 μm or less. From the viewpoint of suppressing the occurrence of defects such as cracks, the thickness can be approximately 10 μm or more, for example, 20 μm or more. The average thickness of the member can be, for example, the average value when the thickness of the member is measured at three or more points (for example, five points).

[0037] (Base material 12) The substrate 12 is not particularly limited as long as the effects of the technology disclosed herein are exhibited, and various substrates can be used, such as substrates made of metal materials and ceramic substrates (e.g., alumina substrates and boron nitride substrates). In particular, substrates made of metal materials are preferred because they can be used for various industrial applications. Examples of such substrates include stainless steel (SUS), carbon steel, copper, and cemented carbide. The thickness of the substrate 12 is not particularly limited, and can be about 0.1 to 10 mm (e.g., about 0.5 to 5 mm).

[0038] <Manufacturing method of item 1> Next, a method for producing the article 1 according to one embodiment will be described. The production method according to this embodiment includes a preparation step (step 1) of preparing a component forming composition, a coating step (step 2) of coating the component forming composition on a substrate, and a firing step (step 3). Each step will be described below.

[0039] Preparation Steps (Step 1): In this step, first, a slurry-like (including ink-like and paste-like) composition for forming a member is prepared, which contains the above-mentioned glass powder, an inorganic filler, and, if necessary, a binder and a dispersion medium. Here, the amount of the glass powder is not particularly limited as long as the effects of the technology disclosed herein are exhibited, but can be within the range of approximately 1 to 20 mass% when the entire composition for forming a member is taken as 100 mass%. In addition, the amount of the inorganic filler is not particularly limited as long as the effects of the technology disclosed herein are exhibited, but can be within the range of approximately 0.1 to 40 mass% when the entire composition for forming a member is taken as 100 mass%.

[0040] The dispersion medium is not particularly limited, and a conventionally known dispersion medium can be appropriately selected and used. Examples include hydrocarbon solvents such as N-methylpyrrolidone (NMP) and cyclohexane; ester solvents such as ethyl acetate, normal propyl acetate, isopropyl acetate, and butyl acetate; ketone solvents such as acetone, methyl ethyl ketone, methyl isobutyl ketone, and cyclohexanone; aromatic hydrocarbon solvents such as toluene and xylene; ether solvents such as hexane, diisopropyl ether, methyl cellosolve, ethyl cellosolve, and 1,4-dioxane; alcohol solvents such as methanol, ethanol, butanol, and isopropanol, and mixtures thereof. The amount of the dispersion medium is not particularly limited as long as the effects of the technology disclosed herein are exhibited, but can be within the range of approximately 20 to 95% by mass when the entire composition for forming a member is taken as 100% by mass.

[0041] The binder is not particularly limited, but for example, a resin material having thermoplasticity and being burned off by a baking process (typically, heating and baking at 200°C or higher) can be suitably used. By adding such a binder, the moldability of the green sheet can be improved. Suitable examples include natural polymer compounds such as carrageenan and xanthan gum, cellulose polymers such as ethyl cellulose and carboxymethyl cellulose, acrylic resins, epoxy resins, phenolic resins, amine resins, and alkyl resins. The amount of the binder is not particularly limited as long as the effect of the technology disclosed herein is exhibited, but can be within the range of approximately 1 to 20% by mass when the entire component forming composition is taken as 100% by mass.

[0042] In addition, conventionally known additives may be added to the composition as long as they do not significantly impair the effects of the technology disclosed herein. Examples of such additives include dispersants, plasticizers, defoamers, release agents, antioxidants, thickeners, pore formers (pore forming materials), etc. The amount of the additives is not particularly limited as long as the effects of the technology disclosed herein are exhibited, but can be within the range of approximately 1 to 10% by mass when the entire composition for forming a member is taken as 100% by mass.

[0043] The above-mentioned component-forming composition can be prepared using various conventionally known stirring and mixing devices such as a ball mill, a mixer, a disperser, and a kneader. For example, the above-mentioned glass powder, inorganic filler, binder, dispersion medium, and additives are charged into any stirring and mixing device, and stirred and mixed for a predetermined time (for example, about 1 to 2 hours), to prepare a homogeneous composition. The viscosity of the component-forming composition is preferably about 50 to 10,000 mPa·sec (25°C-100 rpm) (preferably about 200 to 5,000 mPa·sec). Such a viscosity can be measured, for example, using a commercially available viscometer.

[0044] Coating process (step 2): In this step, the composition for forming a member prepared as described above is then applied onto the substrate as described above. Here, according to conventionally known coating methods (for example, blade coating method, spray coating method, screen printing method, roll compaction molding method, dip coating method, etc.), it was difficult to give the inorganic filler the above-mentioned orientation (i.e., the inorganic filler tended to be arranged randomly). However, as a result of intensive research by the present inventors, it was found that it is possible to give the inorganic filler the above-mentioned orientation by a coating method in which the conditions are appropriately adjusted. A suitable example of such a coating method is a spray coating (electrostatic coating) method in which a composition for forming a member adjusted to an appropriate viscosity (such as the above-mentioned viscosity) is discharged from a nozzle with an appropriate diameter to perform coating. In such a coating method, for example, when the inorganic filler is oriented in the thickness direction of the member (see FIG. 2B), the distance between the nozzle and the work (here, substrate) is shortened and the discharge speed of the composition for forming a member is increased. Furthermore, coating may be performed by narrowing the coating area. On the other hand, for example, when the inorganic filler is oriented in a direction perpendicular to the cross section in the thickness direction of the member (see FIG. 2A), the distance between the nozzle and the workpiece is increased and the discharge speed of the composition for forming the member is slowed down. By such measures, the inorganic filler can be provided with the desired orientation (for details, see the examples described later). After the coating as described above is performed, if necessary, the composition may be dried at a predetermined temperature (e.g., about 100 to 200°C) for a predetermined time (e.g., about 1 to 2 hours) to obtain a precursor of an article in which the component-forming composition is applied onto a substrate.

[0045] Firing process (step 3) In this step, the precursor of the article produced as described above is fired. This produces an article 1 having a base material 12 and a member 10 formed on the base material. The firing temperature in this step can be, for example, about 700°C to 1000°C. The firing time can be, for example, about 1 hour to 5 hours.

[0046] [Other forms] In the above embodiment, an article in which a member is formed on a substrate is described, but the present invention is not limited thereto, and may be, for example, an embodiment in which a member is sandwiched between two substrates (i.e., a sandwich structure). In this case, the member can be produced by applying a composition for forming a member onto a substrate in the same manner as above, drying the substrate, and then stacking another substrate thereon and firing the substrate.

[0047] Test examples relating to the present disclosure will be described below, but it is not intended that the present invention be limited to such test examples.

[0048] <First test example> In this test example, the insulating properties and heat dissipation properties of samples having members containing inorganic fillers with different average aspect ratios were evaluated.

[0049] (Sample Preparation) First, glass powder (average particle size: 0.5 μm), a commercially available inorganic filler (alumina filler, average major axis: 8.0 μm) shown in the corresponding column of Table 1, a binder (acrylic resin), and a solvent (NMP) were kneaded in a mass ratio of 5:0.5:1.5:93. This resulted in a composition for forming a member. Here, the glass powder used had the following composition in terms of molar ratio of oxide: B2O3; 13.3 mol%, Al2O3; 14.6 mol%, SiO2; 20.3 mol%, ZnO; 8.7 mol%, SrO; 0.8 mol%, Y2O3; 1.1 mol%, BaO; 41.2 mol%. The linear thermal expansion coefficient of the glass powder from 30°C to 500°C was measured using a TMA8310 manufactured by Rigaku Co., Ltd., and was found to be 1.0×10 ―5 K ―1 The viscosity of the composition for forming a member was about 2000 mPa·sec (measured at 25°C and 100 rpm using a Brookfield B-type viscometer). When the viscosity was high or low, the amount of solvent was appropriately adjusted.

[0050] Here, the average short diameter of the inorganic filler in each example was 0.04 μm in Example 1, 0.2 μm in Examples 2 and 3, 0.8 μm in Example 4, and 4.0 μm in Example 5. The particles in Examples 6 and 7 were approximately spherical, with average particle diameters of 5.6 μm and 1.0 μm, respectively. Although not specified, the average thickness of the inorganic filler used in the first to third test examples was about 0.01 μm.

[0051] Next, the member-forming composition prepared above was spray-coated (electrostatically applied) onto a substrate (SUS430) measuring 25 mm long x 25 mm wide x 2 mm, and then heat-treated at about 1000°C. In this way, samples according to each example were obtained. The spray coating was performed under the following conditions.

[0052] [Spray coating conditions] Equipment: Nagase Techno Engineering Mist Coater PDR-08 Voltage: 6kV Workpiece temperature: 80℃ Nozzle inner diameter: 300μm For the component forming compositions according to Examples 1, 2, and 4 to 7, the distance between the nozzle and the work (here, SUS430) was 50 mm, and the discharge speed of the component forming composition was 0.05 mL / min. For the component forming composition according to Example 3, the distance between the nozzle and the work was 15 mm, and the discharge speed was 0.1 mL / min. Then, the green sheet after the supply was dried to obtain a sample according to each Example having a component with a thickness of about 50 μm.

[0053] (Evaluation of Orientation Direction of Inorganic Filler) For the samples according to each example obtained as described above, one or more SEM images (magnification: 2000 times) of a cross section (i.e., XY cross section) of 0.05 mm long x 0.03 mm wide in the thickness direction of the member were randomly obtained. Such images were obtained using JSM-6610LA manufactured by JEOL Ltd. Here, in the SEM images according to Examples 1, 2, 4, and 5, it was confirmed that the inorganic filler was arranged in a direction generally perpendicular to the cross section, and in the SEM image according to Example 3, it was confirmed that the inorganic filler was arranged in the thickness direction. In addition, in the SEM images according to Examples 6 and 7, it was observed that the inorganic filler was arranged randomly (i.e., had no orientation).

[0054] Next, the acute angle θ of the major axis of the inorganic filler observed in the SEM images of Examples 1, 2, 4, and 5 with respect to the direction perpendicular to the cross section (θ in the member 10a of FIG. 2A) was a In addition, the acute angle θ (θ in the member 10b in FIG. 2B) formed by the major axis of the inorganic filler observed in the SEM image of Example 3 with respect to the thickness direction was measured. b In each example, the measurement was performed for at least 100 inorganic fillers. As a result, in the SEM images of Examples 1 to 5, the above θ (θ in Examples 1, 2, 4, and 5) was measured for 90% by number or more of the inorganic fillers observed. a ,In Example 3, θ b It was confirmed that the value of the orientation angle (corresponding to ) was 10° or less. The results are shown in the column of "Orientation direction of inorganic filler" in Table 1.

[0055] (Evaluation of heat dissipation) The heat dissipation of the samples according to the examples obtained as described above was evaluated. Specifically, an aluminum plate having the same shape as the sample was heated in a furnace at 400°C under an air atmosphere to stabilize it. Next, the sample was placed on the heated aluminum plate, and then another aluminum plate having the same shape as the sample was placed on it, and the furnace was turned off to stop heating. Next, the temperature of the surface of the aluminum plate placed on the sample that was not in contact with the sample was measured over time, and the time it took to return to room temperature (25°C) was measured. If the time it took to return to room temperature was less than 10 minutes, the heat dissipation was evaluated as "◎", if the time it took to return to room temperature was 10 minutes or more but less than 15 minutes, the heat dissipation was evaluated as "○", if the time it took to return to room temperature was 15 minutes or more but less than 20 minutes, the heat dissipation was evaluated as "△", and if the time it took to return to room temperature was 20 minutes or more, the heat dissipation was evaluated as "×". The results are shown in the "heat dissipation" column of Table 1.

[0056] (Insulation evaluation) The sheet resistance value (Ω / □) of the surface of the member included in each sample according to the examples obtained as described above was measured. For this measurement, a high resistivity meter Hiresta-UP (manufactured by Mitsubishi Chemical Corporation, MCP-HT450) was used. Note that, for this measurement, a ring probe (manufactured by the same company, URS probe, MCP-HTP14) was used and the measurement was performed with a measurement applied voltage of 1000 V. When the sheet resistance value was 1.0×10 14 If the resistance was Ω / □ or more, the insulation was evaluated as "◎" and the sheet resistance was evaluated as 1.0×10 13 Ω / □ or more 1.0×10 14 When the sheet resistance was less than 1.0×10 12 Ω / □ or more 1.0×10 13 If the resistance was less than Ω / □, the insulation was rated as "△" and the sheet resistance was 1.0×10 12 When the resistance was less than Ω / □, the insulation was marked as “×.” The results are shown in the “Insulation” column of Table 1.

[0057] Furthermore, although not shown in Table 1, it was found that when the alumina of Example 4 was used and no orientation was provided, the insulation properties were ensured but the heat dissipation properties were not favorable.

[0058] [Table 1]

[0059] <Second test example> In this test example, the insulation properties and heat dissipation properties of samples having members containing inorganic fillers with different average minor axis / major axis values ​​were evaluated.

[0060] (Sample Preparation) First, the same glass powder as above, a commercially available inorganic filler (alumina filler, average aspect ratio: 0.02) shown in the corresponding column of Table 1, a binder (acrylic resin), and a solvent (NMP) were kneaded in a mass ratio of 5:0.5:1.5:93. This resulted in a component-forming composition. The viscosity of the component-forming composition was about 2000 mPa·sec (measured at 25°C, 100 rpm with a Brookfield B-type viscometer).

[0061] Here, the average minor axis diameter of the inorganic filler in each example was: Example 8: 0.01 μm, Example 9: 0.02 μm, Example 10: 0.1 μm, Example 11: 0.16 μm, Example 12: 0.4 μm, and Example 13: 0.6 μm.

[0062] Next, the composition for forming a member prepared as described above was spray-coated onto a substrate (SUS430) measuring 25 mm long x 25 mm wide x 2 mm thick under the same conditions as in Example 1 of the first test example (i.e., conditions in which the inorganic filler is oriented in a direction perpendicular to the cross section in the thickness direction of the member), and then heat-treated at about 1000° C. As a result, samples according to each example having a member with a thickness of about 50 μm were obtained.

[0063] (Evaluation of heat dissipation) The heat dissipation properties of the samples according to each example were evaluated in the same manner as in Test Example 1. The results are shown in the "Heat Dissipation Properties" column of Table 2.

[0064] (Insulation evaluation) The insulating properties of the samples according to each example were evaluated in the same manner as in Test Example 1. The results are shown in the "Insulating Properties" column of Table 2.

[0065] [Table 2]

[0066] <Third Test Example> In this test example, the area occupancy rate of the inorganic filler in the cross section in the direction perpendicular to the cross section in the thickness direction of the member obtained when the content of the inorganic filler was changed was calculated. Then, the bonding strength between the member and the substrate according to each example was evaluated. In addition, the insulation property and heat dissipation property of the sample equipped with each member were also evaluated.

[0067] (Sample Preparation) First, the same glass powder as above, a commercially available inorganic filler (alumina filler, average aspect ratio: 0.02, average short diameter: 0.2 μm, average long diameter: 8.0 μm), a binder (acrylic resin), and a solvent (NMP) were kneaded. Here, when the entire composition for forming a member was taken as 100 mass%, the glass powder was 5 mass%, the inorganic filler was the mass% shown in the corresponding column in Table 1, the binder was 1.5 mass%, and the remainder was the solvent. In this way, a composition for forming a member was obtained. Here, the viscosity of the composition for forming a member was about 2000 mPa·sec (measured at 25°C-100 rpm with a Brookfield B-type viscometer). In addition, when the viscosity was high or low, it was dealt with by appropriately adjusting the amount of the solvent. Next, the composition for forming a member prepared as described above was spray-coated onto a substrate (SUS430) measuring 25 mm long x 25 mm wide x 2 mm thick under the same conditions as in Example 1 of the first test example (i.e., conditions in which the inorganic filler was oriented in a direction perpendicular to the cross section in the thickness direction of the member), and then heat-treated at about 800° C. As a result, samples according to each example having a member with a thickness of about 50 μm were obtained.

[0068] (Evaluation of heat dissipation) The heat dissipation of the samples according to each example was evaluated in the same manner as in Test Example 1. The results are shown in the "Heat Dissipation" column of Table 3.

[0069] (Insulation evaluation) The insulating properties of the samples according to each example were evaluated in the same manner as in Test Example 1. The results are shown in the "Insulating Properties" column of Table 3.

[0070] (Measurement of area occupancy rate of inorganic filler) For the samples according to each example obtained as described above, the proportion of the area occupied by the inorganic filler was measured in the SEM image of the cross section in the direction perpendicular to the cross section in the thickness direction of the member. Specifically, the glass part and the inorganic filler part were binarized from the obtained SEM image, and the area ratio of the inorganic filler to the total area was taken as the area occupancy rate of the inorganic filler. This measurement was performed using JSM-6610LA manufactured by JEOL Ltd., in an observation area of ​​2000 times (backscattered electrons) by SEM.

[0071] The image analysis software used was Image-Pro Plus manufactured by Nippon Roper Co., Ltd. In this image analysis, first, the area was calculated by tracing the outline of the inorganic filler part. The outline of the inorganic filler was traced on the contrast-adjusted SEM. This contrast adjustment can be performed automatically by using the "optimized contrast adjustment" command of the image analysis software. In addition, the inorganic filler part can be separated and extracted from the background with high accuracy by using the binarization "Segmentation (color extraction)" command. Specifically, for example, in binarization, the image is converted into a black-and-white image in which the contrast-adjusted inorganic filler is white. The area occupancy rate was calculated based on the following formula: area occupancy rate = (total area of ​​inorganic filler part) / (total area of ​​observation field) x 100 (%), which is the total number of pixels of the part where the pixel corresponding to the inorganic filler is a mass of 50 pixels or more / the total number of pixels of the observation field. The results are shown in the "area occupancy rate of inorganic filler" column in Table 3.

[0072] (Evaluation of bonding strength) In order to evaluate the adhesion between the sample and the substrate, a cross-cut test was carried out according to JIS K5600-5-6:1999 (General test methods for paints, Part 5: Mechanical properties of coatings, Section 6: Adhesion (cross-cut method)). First, a grid pattern of 25 squares was formed by making six parallel cuts at intervals of 1 mm at a position 5 mm or more away from the end of the sample. Then, a transparent pressure-sensitive adhesive tape (adhesive strength 4.01 N / mm) with a width of 24 mm was applied to cover the grid pattern, and the tape was peeled off in a direction that made an angle of about 60°. The area ratio of the peeled part (missing part area ratio) x (%) of the total area (25 squares) of the cross-cut was calculated. As shown below, the evaluation code corresponding to the missing part area ratio x of the sample is shown in the "Adhesion" column of Table 2. The evaluation symbols below roughly correspond to the evaluation scores of the Japan Paint Inspection Association's cross-cut test, with "X" corresponding to 2 points or less, "△" corresponding to 4 points, "◯" corresponding to 6 points, and "◎" corresponding to 8 to 10 points.

[0073] Although not shown in Table 3, the samples prepared using the member-forming composition not containing an inorganic filler were rated "x" for both heat dissipation and insulation.

[0074] [Table 3]

[0075] As shown in Table 1, in the samples according to Examples 1 to 5, which include a substrate (here, SUS430) and a plate-like member formed on the substrate and containing a glass matrix and an inorganic filler, the inorganic filler has an average aspect ratio (minor axis / major axis ratio) of 0.005 to 0.5, and 90% or more of the inorganic fillers observed in an SEM image of a cross section in the thickness direction of the member have an acute angle θ of 10° or less between the major axis of the inorganic filler and either the thickness direction or the direction perpendicular to the cross section. It was confirmed that the samples according to Examples 6 and 7, in which the inorganic filler has an average aspect ratio outside the above range and does not have orientation, can preferably achieve both insulation and heat dissipation. Also, referring to the evaluation results of the samples according to Examples 2 and 3, it was confirmed that the heat dissipation is superior when the inorganic filler is oriented in the thickness direction of the member.

[0076] As shown in Table 2, it was confirmed that the samples according to Examples 9 to 12, in which the inorganic filler had an average major axis value of 1 μm to 20 μm, more suitably achieved both heat dissipation properties and insulating properties compared to the samples according to Examples 8 and 13, in which the inorganic filler had an average major axis value outside the above range. Moreover, it was confirmed that, among the samples according to Examples 9 to 12, the samples according to Examples 10 to 12, in which the average major axis value was 5 μm or more, had particularly excellent insulating properties. Furthermore, as shown in Table 3, in SEM images of the cross section of the component in a direction perpendicular to the cross section in the thickness direction of the component, the samples of Examples 15 to 21 in which the proportion of the area occupied by the inorganic filler (i.e., the area occupancy rate) is within the range of 15 to 70% were confirmed to have excellent bonding properties between the substrate and the component in addition to achieving both heat dissipation properties and insulation properties, compared to the samples of Examples 14 and 22 in which the area occupancy rate of the inorganic filler is outside the above range.

[0077] As described above, the technology disclosed herein can provide an article having a member that can favorably achieve both insulation and heat dissipation even in a thin layer (about 50 μm in this test example). Such an article can be used for various industrial applications. [Explanation of symbols]

[0078] 1 article 10, 10a, 10b Materials 12 Base material 20, 20a, 20b Inorganic filler

Claims

1. A substrate; a plate-like member including a glass matrix and an inorganic filler formed on the substrate; An article comprising: The inorganic filler has an average aspect ratio (minor axis / major axis ratio) of 0.005 to 0.5; An article, wherein, for 90% or more by number of the inorganic fillers observed in an SEM image of a cross section in the thickness direction of the member, the acute angle θ of the major axis of the inorganic filler in either the thickness direction or a direction perpendicular to the cross section is within 10°.

2. The article according to claim 1 , wherein the inorganic filler has an average minor axis value of 0.01 μm or more and an average major axis value of 20 μm or less.

3. The article according to claim 1 or 2, wherein the average value of the major axis is within a range of 1 μm to 20 μm.

4. The ratio of the area occupied by the inorganic filler in an SEM image of a cross section of the member in a direction perpendicular to the cross section in the thickness direction is calculated using the following formula: Area Occupancy Rate=(Total Area of ​​Inorganic Filler / Total Area of ​​Observation Field)×100(%) The article according to any one of claims 1 to 3, wherein the area occupancy rate is within a range of 15 to 70% when calculated based on the above formula (1).

5. The glass powder constituting the glass matrix is ​​B 2 O 3 -SiO 2 The article of any one of claims 1 to 4, comprising a vitreous glass.

6. The thermal expansion coefficient of the glass powder constituting the glass matrix from 30° C. to 500° C. is 0.3×10 ―5 K ―1 ~2.0 x 10 ―5 K ―1 The article according to any one of claims 1 to 5, wherein

7. The article according to any one of claims 1 to 6, wherein the substrate is made of a metallic material.

8. The article according to any one of claims 1 to 7, wherein the member has an average thickness of 100 µm or less.

Citation Information

Patent Citations

  • Bonded ceramics and iron parts and production thereof

    JP1990225383A

  • Membranous inorganic material

    JP2013079157A

  • Composition, green sheet, burned product, and glass ceramic substrate

    JP2020019688A

  • Glass ceramic substrate and housing for portable electronic equipment using substrate

    WO2014073604A1